Risk Management Practices and Financial Performance: The Case of Sultanate of Oman: Praktik Manajemen Risiko dan Kinerja Keuangan: Kasus Kesultanan Oman - AL Mamari, Shima Hamdan; Al Ghassani, Ahad Said; Ahmed, Essia Ries (Universitas Muhammadiyah Sidoarjo, 2022)
The main objective of this study is to test the relationship between risk management practices and bank's financial performance. This is quantitative study, where the quantitative data was collected via secondary data. Data collection from the annual reports of eight banks listed in Muscat Stock Exchange (MSX). In this research, data collected is analyzed using Structural Equation Modelling (SEM) with Partial Least Square PLS Software. The findings revealed that risk management is positively meaningful while avoiding risk .The findings pointed that the risk management has significant relation with a ROA. This result indicates that management has a significant influence on banks performance (ROA). As well as, the findings found that the risk management insignificantly related to a (ROE).